From algorithm outputs to classroom impact: A conversation with Marian Abu, director of teacher management at the Teaching Service Commission - Frazer, Madleen Madina (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _EdTechHub_Output; _r:AddedByMyEducationEvidence

An EdTech reading list from the Helpdesk team: Autumn 2020 (EdTech Hub, 2020)
In this blog post, we summarise six new publications from the Helpdesk and what we have learned about monitoring and evaluation, curriculum reform, blended learning, and teacher education. As Covid-19 continues to affect learning around the world, our Helpdesk is seeing a shift in the requests we receive. Earlier, the bulk of requests were linked to short-term Covid responses. Now,…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH